Transient aspects of plasma luminescence induced by triboelectrification of polymers - Puhan,D; Nevshupa,R; Wong,J; Reddyhoff,T (Tribology International, 2019)
Transient electric gas discharges that occur around sliding interfaces during contact electrification of polymers were studied at millisecond timescales and with micrometre resolution. Deduced vibrational temperatures indicate cold plasma resulting from positive corona discharge. At millisecond timescales, previously unseen rapid discharge events are observed, and modelling suggests that these result from streamer development, triggered by electron emission from the polymer surface. Those which occur over a period of several seconds are shown to be caused by competition between charge generation and the formation of polymer films. The findings explain the interplay between charging and plasma generation and their dependence on wear processes.